2020
DOI: 10.48550/arxiv.2001.02613
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Don't Forget The Past: Recurrent Depth Estimation from Monocular Video

Abstract: Autonomous cars need continuously updated depth information. Thus far, the depth is mostly estimated independently for a single frame at a time, even if the method starts from video input. Our method produces a time series of depth maps, which makes it an ideal candidate for online learning approaches. In particular, we put three different types of depth estimation (supervised depth prediction, self-supervised depth prediction, and self-supervised depth completion) into a common framework. We integrate the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…This allows for modelling the relations between the frames, even without knowledge of the camera poses. Several single image depth prediction methods [36,47,54] have shown that ConvLSTM cells can improve the temporal consistency of the depth predictions.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…This allows for modelling the relations between the frames, even without knowledge of the camera poses. Several single image depth prediction methods [36,47,54] have shown that ConvLSTM cells can improve the temporal consistency of the depth predictions.…”
Section: Related Workmentioning
confidence: 99%
“…In [36], input frames and sparse depth cues are encoded together, then temporal relations between encodings are modeled through ConvLSTM. Finally, the depth predictions are output by a decoder.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, research on monocular depth estimation by self-supervised learning has become an important field in deep learning [4,38,14,27,45,46,44,47,20,48,41]. The developments in spatial transformer modules have further enhanced research on monocular depth estimation [19].…”
Section: Related Workmentioning
confidence: 99%